A Study on Consumers’ Travel Purchase Intention Through Travel Apps - Mishra, Rajiv; Sharma, M. P.; Seth, Kunal; Singh, Vikas (Prabandhan: Indian Journal of Management, 2023)
Purpose : The present study identified the factors influencing consumer travel purchase intention. The primary goal of this study was to ascertain if Indian users of travel applications can use the restrictions derived from the expanded unified theory of acceptance and usage of technology with perceived trust as a mediating variable. The article further addressed the empirical findings and implications of practical work to the conclusion of this study. Methodology : Using UTAUT2 as a base model, this study investigated customers’ desire to purchase things using travel applications. A representative survey of 261 participants was obtained. Findings : The results indicated that all five were supported among the four constructions. The results revealed that EE (effort expectancy) had the most significant impact on purchase intention, followed by FC, PE, and SI. Overall, this work will benefit travel application businesses in promoting their corporate and marketing objectives. The results showed that effort expectancy had a strong relationship with purchase intention. Practical Implications : Using UTAUT2 as a base model, the study investigated customers’ desire to purchase things using travel applications. With this study, app development executives can foresee the continuing use of travel apps for good marketing, user engagement, and advertisement inside devices. Using UTAUT2 as a base model, this study investigated customers’ desire to purchase things using travel applications. Originality : Limited empirical studies have explored travellers’ adoption of mapping apps. This study included the conceptual framework in the perceived trust variable to explain the effects of the UTAUT2 system’s fundamental ideas, such as performance expectancy, social influence, and enabling situations. In contrast, in other related studies, effort expectancy has been thought to explain the direct impact on the willingness of consumers to buy travel products through travel apps.